Comparison of chemiluminescent heterogeneous and homogeneous–heterogeneous assays coupled with isothermal circular strand-displacement polymerization reaction amplification for the quantification of miRNA-141. Issue 19 (24th August 2022) - Solovjev, Anton M.; Galkin, Ivan I.; Medved'ko, Alexey V.; Pletjushkina, Olga Yu.; Zhao, Shulin; Sakharov, Ivan Yu.
Abstract : A heterogeneous and homogeneous–heterogeneous chemiluminescent microplate assay was developed for the determination of miRNA-141 levels in human cells. Abstract : Heterogeneous and homogeneous–heterogeneous assays for the quantitation of hsa-miR-141-3p (miRNA-141) were constructed. Both microplate assays were based on the use of the isothermal circular strand-displacement polymerization reaction (ICSDPR), which was carried out in heterogeneous and homogeneous media, respectively. In addition, a streptavidin-polyperoxidase conjugate and enhanced chemiluminescence were used to increase the assay's sensitivity. A comparison of the developed assays showed that the sensitivity of the heterogeneous assay was higher than that of the homogeneous–heterogeneous assay. The detection limit values of the heterogeneous and homogeneous–heterogeneous assays were 51 fM and 10 pM, respectively. The amplification index for the ICSDPR used in the heterogeneous assay of miRNA-141 was 100. Using miRNAs of the miRNA-200 family, the high specificity of the assay was demonstrated. MiRNA-141 in human cultured cells was determined by the heterogeneous ICSDPR-assisted assay with chemiluminescence detection. To assess the purification yield of miRNAs from cellular lysates, the heterogeneous assay of miRNA-39 developed on the same platform was used. The intracellular content of miRNA-141 in Caco-2, HepG2, MCF-7 and HeLa was shown to be 3400, 1400, 1300 and 470 copies per cell, respectively.